Silane as pretreatment for protection of steel - Pisesale, Julieta (2013)
Steel has been used as structural material for ages although it interacts with the environment loosing its main important property. The aim of this research was to study different times of silane hydrolysis in order to obtain better anticorrosive protection of steel. The substrates employed were sandblasted steel and sandblasted steel exposed to the salt spray chamber in order to oxidize the substrate and evaluate the performance of the silane on a not‐so‐well prepared surface. Electrochemical tests such as polarization curves and corrosion potential measurements were done on the pretreated metal. Results showed the silane film protect steel even when the surface preparation was not adequate.